2021
DOI: 10.1007/s10551-021-04884-3
|View full text |Cite
|
Sign up to set email alerts
|

E-Commerce and Consumer Protection in India: The Emerging Trend

Abstract: Given the rapid growth and emerging trend of e-commerce have changed consumer preferences to buy online, this study analyzes the current Indian legal framework that protects online consumers' interests. A thorough analysis of the two newly enacted laws, i.e., the Consumer Protection Act, 2019 and Consumer Protection (E-commerce) Rules, 2020 and literature review support analysis of 290 online consumers answering the research questions and achieving research objectives. The significant findings are that a secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 69 publications
2
62
1
3
Order By: Relevance
“…Because of its ease of use, comfort, and cost-efficiency, e-commerce has become an essential buying tool for customers worldwide. Different facets, such as the social nature of e-commerce, appear to influence online purchase intentions (Chawla & Kumar, 2021;Hassan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its ease of use, comfort, and cost-efficiency, e-commerce has become an essential buying tool for customers worldwide. Different facets, such as the social nature of e-commerce, appear to influence online purchase intentions (Chawla & Kumar, 2021;Hassan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With the growing importance of online sales and the rise in the number of online shoppers, marketers and academics have focused their interest on better understanding online purchases behaviorally, and there is a significant opening that requires deliberation (Kumar, & Ayodeji, 2020;Tokar et al, 2021). E-commerce is more economical and convenient than offline shopping (Chawla, & Kumar, 2021). Therefore, several issues need to be highly concerned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although social commerce has achieved tremendous success since it was coined as a new form of business practices, it is reported that almost half of social media users showed no purchase intention on social commerce websites ( Ko, 2018 ). More evidences have been found that people are not necessarily influenced by their peers using social media for online shopping behaviors because of potential negative effects including poor customer service and websites quality ( Gutama et al, 2021 ), inaccurate information, privacy disclosure and fraud on consumers ( Lickel et al, 2000 ; Mikalef et al, 2017 ; Paireekreng et al, 2019 ; Wang and Herrando, 2019 ; Chawla and Kumar, 2021 ). In other words, users’ purchase intention is not equally influenced by their connections with other users shopping online, and the behavior of using social media does not necessarily increase the likelihood of users’ purchase on social commerce websites ( Kim and Park, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…After globalization, E-commerce (electronic commerce) plays a vital role in the business world with rapid development and popularization because of advancement and emerging of technologies as well as consumers purchasing power and internet users (Chawla and Kumar, 2021 ). E-commerce is the electronic buying or selling of goods via internet services.…”
Section: Introductionmentioning
confidence: 99%